2023
DOI: 10.3390/molecules28145587
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Characterization, and Evaluation of the Cytotoxic Activity of Piperine in Its Isolated form and in Combination with Chemotherapeutics against Gastric Cancer

Abstract: Gastric cancer is one of the most frequent types of neoplasms worldwide, usually presenting as aggressive and difficult-to-manage tumors. The search for new structures with anticancer potential encompasses a vast research field in which natural products arise as promising alternatives. In this scenario, piperine, an alkaloid of the Piper species, has received attention due to its biological activity, including anticancer attributes. The present work proposes three heating-independent, reliable, low-cost, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…Research has shown that piperine antimicrobial activity and cytotoxicity effects can be verified through molecular modeling. [ 33 , 34 ] Additionally, molecular modeling can also confirm the clinical therapeutic effects of different components such as geissoschizoline N4-methylchlorine and Eleutherine plicata by simulating molecular docking. [ 35 , 36 ] Consequently, in silico modeling offers the potential to develop new drug candidate ingredients with targeted effects.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that piperine antimicrobial activity and cytotoxicity effects can be verified through molecular modeling. [ 33 , 34 ] Additionally, molecular modeling can also confirm the clinical therapeutic effects of different components such as geissoschizoline N4-methylchlorine and Eleutherine plicata by simulating molecular docking. [ 35 , 36 ] Consequently, in silico modeling offers the potential to develop new drug candidate ingredients with targeted effects.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive grasp of these mechanisms is vital for a holistic understanding of how inflammation influences gastric cancer pathogenesis. [ 42 44 ] The objective of the present study was to utilize a two-sample Mendelian randomization analysis, incorporating data from genome-wide association studies (GWAS), to probe the causal nexus between inflammatory biomarkers and the risk of gastric malignancy. By doing so, it seeks to uncover innovative avenues for the early prevention and management of GC, while also providing empirical guidance for the clinical treatment of gastric malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The attention given to the study of this molecule is mainly due to its biological properties, such as: anti-inflammatory, antioxidant, immunomodulatory and anticancer, properties which allow this compound to chemically interact with various molecular targets. Specifically, in relation to piperine's anticancer activity, recent observations have shown that its mechanism of action is multiple and involves the activation of cell signaling pathways, such as cell proliferation, programmed cell death, decreased migration and invasion of cancer cells [7].…”
Section: Introductionmentioning
confidence: 99%